2011
DOI: 10.5539/jas.v3n2p157
|View full text |Cite
|
Sign up to set email alerts
|

Shrimp Drying Characterizes Undergoing Microwave Treatment

Abstract: In this paper, a laboratory microwave oven was used to dry the shrimp, applying microwave power in the four levels of 200, 300, 400 and 500W. Results indicated that drying took place in the falling rate period. The drying rate increased with drying microwave power, but decreased with moisture content. The effective diffusivity varied from 1.54×10 -10 to 1.43×10 -9 m 2 /s. About 22.54% increase in drying efficiency and about 28.94% (0.937MJ/kg[H 2 O]) decrease in specific energy consumption could be obtainable … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Meanwhile, there is a little energy loss during microwave heating for most of the microwave energy can be absorbed by the samples. Consequently, the microwave heating can bring many benefits such as drying time being shortened, high thermal efficiency, economical space utilization, more sanitary environment, precise process control, fast start-up and shut-down operations, compared to the convective drying [7,8]. Moreover, the volatile matter of the coal is hardly affected by microwave treatment at power levels between 5 and 10 kW [9].…”
Section: Introductionmentioning
confidence: 99%
“…Meanwhile, there is a little energy loss during microwave heating for most of the microwave energy can be absorbed by the samples. Consequently, the microwave heating can bring many benefits such as drying time being shortened, high thermal efficiency, economical space utilization, more sanitary environment, precise process control, fast start-up and shut-down operations, compared to the convective drying [7,8]. Moreover, the volatile matter of the coal is hardly affected by microwave treatment at power levels between 5 and 10 kW [9].…”
Section: Introductionmentioning
confidence: 99%
“…Drying time, water activity, and rehydration ratio were selected as the response variables. The levels were selected based on literature reviews (Darvishi et al, 2012; Farhang et al, 2011; Lee et al, 2021). A three‐factor, three‐level BBD experimental design was used in optimizing the drying conditions for shrimp in a hot air‐assisted microwave (HAMW) drying system.…”
Section: Methodsmentioning
confidence: 99%
“…They reported that microwave drying showed an increase in protein contents since it had less effect on the amino acid composition of grass carp fillets. Microwave drying of shrimp increased drying efficiencies to about 22.54% and reduced specific energy consumption to about 28.94%, by increasing MW power from 200 to 500 W (Farhang et al, 2011). Drying under the microwave (MW) was found to lower drying time and enhance energy efficiency (Soysal et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Such conditions produce modifications on the structural and biochemical components, which affects the sensory quality of the product (Hernández‐Becerra, Ochoa‐Flores, Soto‐Rodriguez, Rodriguez‐Estrada, & García). Others methods of water removal used for processing shrimp are as follows: superheated steam (Prachayawarakorn et al., 2002), jet‐spouted bed (Niamnuy et al., 2007), heat pump (Guochen et al., 2009), microwave (Farhang et al., 2011), infrared (Tirawanichakul et al, 2008), and electrohydrodynamic (Bai & Sun, 2011) drying, as well as the freeze‐drying (Donsì et al, 2001). However, although these methods offer certain advances in shrimp drying, the most commonly used methods for processing shrimp are still the conventional sun drying and hot air drying (Akonor et al., 2016).…”
Section: Introductionmentioning
confidence: 99%